Market, Hierarchy, and Trust: The Knowledge Economy and the Future of Capitalism - Adler, Paul S. (Organization Science, 2001)
Recent conceptualizations of trends in the structure of U.S. industry have focused on the relative importance of markets, hierarchies, and hybrid intermediate forms. This paper advances the discussion by distinguishing three ideal-typical forms of organization and their corresponding coordination mechanisms: market/price, hierarchy/authority, and community/trust. Different institutions combine the three forms/mechanisms in different proportions. Economic and organizational theory have shown that, compared to trust, price and authority are relatively ineffective means of dealing with knowledge-based assets. Therefore, as knowledge becomes increasingly important in our economy, we should expect high-trust institutional forms to proliferate. A review of trends in employment relations, interdivisional relations, and interfirm relations finds evidence suggesting that the effect of growing knowledge-intensity may indeed be a trend toward greater reliance on trust. There is also reason to believe that the form of trust most effective in this context is a distinctively modern kind—“reflective trust”—as opposed to traditionalistic, “blind” trust. Such a trend to reflective trust appears to threaten the privileges of currently dominant social actors, and these actors' resistance, in combination with the complex interdependencies between price, authority, and trust mechanisms, imparts a halting character to the trend. But the momentum of this trend nevertheless appears to be self-reinforcing, which suggests that it may ultimately challenge the foundations of our capitalist form of society while simultaneously creating the foundations of a new, postcapitalist form.